Strategi Edukasi Budaya Digital dan Keamanan Siber bagi Pelaku UMKM Perempuan di Boja - Fidyah Yuli Ernawati; Rokhmad Budiyono; Evinta Amalia; Sukarsono Sukarsono (Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the understanding and skills of female MSMEs in Boja in implementing Digital Literacy, particularly in aspects of digital culture and cybersecurity. The main problems faced were a lack of understanding of digital media ethics, personal data protection, and the ability to identify cybercrime threats. The activity was implemented through several stages, namely needs assessment, participatory training, and ongoing mentoring. The training activities used a hands-on approach, group discussions, and case simulations to increase participant engagement. The results of the activity showed an increase in participant understanding and awareness of the importance of using digital technology safely and wisely. In addition, participants began to be able to implement basic digital security practices in business activities, such as more secure account management and increased vigilance against online fraud. Thus, the implemented educational strategy has proven effective in improving the digital culture and cybersecurity awareness of female MSMEs in Boja. This activity is expected to support the strengthening of MSME capacity in facing the challenges of sustainable digital transformation.